THE IMPACT OF WORK DISCIPLINE AND WORK ENVIRONMENT ON THE PERFORMANCE OF SHIP CREW MEMBERS (ABK) ABOARD THE MV SINAR PENIDA - Destruly Mangatur (Asosiasi Dosen Muda Indonesia, 2024)
The performance of the crew (ABK) aboard the MV Sinar Penida is influenced by several factors, including work discipline and the work environment. Effective work discipline is thought to enhance efficiency and quality, while a supportive work environment is expected to boost welfare and job satisfaction. This study seeks to thoroughly assess the impact of work discipline and work environment on crew performance. Employing a descriptive quantitative research approach, this study examines two independent variables—work discipline and work environment—and one dependent variable—work performance. The population under study consists of 65 ABK members from the MV Sinar Penida ship. Data analysis is conducted using SPSS, involving tests for normality, classical assumptions, and hypothesis testing. The findings reveal that work discipline has a significant partial effect on the work performance of the MV Sinar Penida crew, whereas the work environment does not show a significant partial impact. However, both work discipline and work environment together significantly influence the work performance of the crew on the MV Sinar Penida.